Enhancing the Students’ Reading Comprehension Achievement through Skimming and Scanning Techniques in Senior High School - Arifitriyanti, Ikhlasil Amalia; Wijaputra, Bambang Arya; Sukmaantara, I Putu (English Education Study Program, 2021)
This research was intended to enhance the students’ participation and reading comprehension achievement by using Skimming and Scanning Techniques at MAN 1 Jember that was conducted collaboratively with the English teacher. The design of the research was classroom action research. The research participants was the X IPA 4 grade students of MAN 1 Jember. The implementation of skimming and scanning techniques could improve the tenth IPA 4 grade students’ active participation in the reading teaching learning process. The result of the observation showed that the percentage of students’ active participation improved from 75.76% in meeting 1 to 78.79% in meeting 2. Furthermore, the implementation of skimming and scanning techniques could enhance the tenth IPA 4 grade students’ reading comprehension achievement in the reading teaching learning process. The result of the reading test showed that the percentage of the students who got at least 75 was 78.79% or 26 students of 33 students. Based on the result above, it could be concluded that both the result of observation and reading comprehension achievement test had achieved the success criteria of this classroom action research in cycle 1.